Penerapan Model Pembelajaran Problem Based Learning Menggunakan Pendekatan Berdiferensiasi dalam Meningkatkan Motivasi dan Kerjasama Peserta didik di Kelas XI F SMAN 15 Pekanbaru - Amratul Wahyunus; Julio Alfath; Sri Oktavia, Yulia Rahma Dani; Asyrul Fikri, Korina Susanti (STKIP Subang, 2025)
This study aims to analyze the effectiveness of the implementation of the Problem Based Learning (PBL) learning model with a differentiation approach in improving student motivation and cooperation in class XI , Senior High School 15 Pekanbaru. The background of this study is the initial observation that shows low motivation and level of student cooperation in learning. The differentiation approach is integrated into the PBL stages to accommodate the diversity of student characteristics. The research method used is Classroom Action Research (CAR) which is carried out in two cycles. Data were collected through learning motivation questionnaires, observation sheets, actions, and student reflections. The results of the study showed that the implementation of the PBL learning model with a differentiation approach succeeded in improving student motivation and cooperation. The results of this study showed a significant increase in learning motivation. In the pre- cycle, the average total student motivation was only 2.54. After the implementation of PBL in Cycle I, the average motivation increased to 3.12, and in Cycle II it increased again to 3.88.